Limit theorems for solutions of stochastic equations with periodic coefficients - Makhno, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We prove theorems on the behavior of solutions of stochastic equations with periodic coefficients and integral functionals of these solutions as time infinitely increases.